Evaluation of transgenic rootstocks regarding their effects on the fruit quality in apple - Muneer, Faraz (2011)
Plant biotechnology has played an important role in plant breeding for introducing desired characteristics into cultivars. This technique is particular important for improving apple cultivars as it can considerably reduce the breeding time. Through genetic engineering, it is possible to change only one gene which is responsible for one desirable character. Apple semi-dwarf rootstock M26 was previously transformed with the rolB gene and showed a greatly increased rooting capacity. A field trial was established in Alnarp to evaluate the effects of these rolB transgenic M26 and M9 rootstocks on growth and development of non-transgenic apple cultivars grafted onto them. It was especially important to evaluate if the fruit quality was affected by the transgenic rootstocks; because fruit quality is of great concern to the apple consumers, which in turn affect the market value of the variety. In this report, the fruit quality was analyzed for the cultivars Elise, Elstar and Jonagold grafted on one rolB transgenic clone of rootstock M26 and two transgenic clones of M9 with the rolB gene, named rolB1 and rolB2, as well as non-transgenic M26 and M9 as controls. Quality parameters analyzed include fruit size, fruit weight, fruit colour, firmness, acidity (TA), total soluble solids (TSS) and ratio of TSS to TA, vitamin C and total phenols. The results showed that Elise on M26 and M26 (rolB) had greater size than those on transgenic and non-transgenic M9. The amount of acidity of Jonagold on M26 (rolB) was significantly higher as compared to M26. M26 (rolB) had higher TSS in Elise than non-transgenic M26, M9 and transgenic M9 (rolB1) The fruit firmness was significantly higher in M9 and M9 (rolB2) both in case of Elise and Elstar than non-transgenic M26, M9 and transgenic M9 (rolB1). Ratio of TSS/acidity was higher in M9 (rolB1) in variety Elstar than non-transgenic M26, M9 and transgenic M26(rolB). There was no significant difference in total phenols either in the peel or the pulp, except in case of M26 (rolB), in peel of Elise, which was significantly lower than M26, M9, M9 (rolB1) and M9 (rolB2). Vitamin C content was significantly lower in M26 than in other transgenic M26 (rolB), M9 (rolB1) and M9 (rolB2) in Elise. The conclusion from this study is that the rolB does not seem to affect the quality of fruit negatively; therefore it can be used for improving the rooting ability of apple rootstocks and for increasing the production potential for the plants.